The Relationship Between Linguistic Features and Psychological States: A Quantitative Approach - Xintong, Zhou; Xiaofei, He (Medical Research Archives, 2024)
Linguistic features are crucial in identifying psychological states. Prior studies have attempted to investigate the influence of psychological states on individual language usage through quantitative analysis, as well as which linguistic features can effectively indicate an individual’s psychological state. Conducting a systematic review of pertinent literature, this study initially outlines the linguistic features related to psychological states extracted quantitatively, encompassing three dimensions: vocabulary, syntax, and emotion. Subsequently, it summarizes the correlations between linguistic features across different levels and psychological states based on quantitative methods. Last, the limitations of existing research are discussed. This study contributes to a deeper understanding of the rationale, significance, and applicability of applying linguistic features in detecting psychological states and provides guidance for future research in this domain.